Mutations in exocyst complex subunit SEC6 gene impaired polar auxin transport and PIN protein recycling in Arabidopsis primary root - Tan, Xiaoyun (Plant science : an international journal of experimental plant biology, 2016)
Copyright © 2016 Elsevier Ireland Ltd. All rights reserved.